Konsep Keberagamaan Orang Cina - M. Ikhsan Tanggok (Refleksi: Jurnal Kajian Agama dan Filsafat, 2005)
The concept of religiosity among the Chinese refers to the traditional Chinese religions that have existed since 600 BC. These religions are still practiced by Chinese people wherever they are, including in Indonesia. By referring to the theory of great tradition and little tradition proposed by Robert Redfield and further developed by Jochim, this article aims to demonstrate that, although Chinese people have embraced religions outside of their traditional beliefs, the teachings of traditional religions and ancestors are still preserved. However, all of this remains within the boundaries they believe do not contradict the official religion they also adhere to.